The sharing economy and management of a sustainable environment in the tourism sector on a global scale - Genç, Ruhet (Turyzm/Tourism, 2019)
The paper will discuss the impact of development of sharing economy on ecological sustainability for the tourism sector at global scale since the main focus in the literature is generally limited to economic and social impacts. It will provide a mathematical model in order to measure the impact of the sharing economy on the welfare of individuals who take part in particular tourism destinations as well as providing benefits for other individuals as a positive external outlook. The development of the model will be dependent on the findings obtained in this study. The results will show that the sharing economy together with collaborative consumption in the tourism sector is an increasing trend in global economy that contributes to ecological sustainability as well. By sharing the means of production, transportation, communication etc both tourists and service providers are capable of decreasing their ecological footprints. In conclusion the paper will contribute to the literature by filling a gap with respect to the lack of connection between environmental sustainability and sharing economy in tourism sector.